Transcriptomic Analysis of Non-Specific Immune Responses in the Rice Field Eel (Monopterus albus) Infected with Pallisentis (Neosentis) celatus - Qin Lei; Xiaoling Li; Hao Wu; Yiwen Wan; Yukun Xie; Jinwei Gao; Wenwen Suo; Ming Zeng; Lingli Liu; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes)
Parasitic infestations present significant threats to the physiological health and ecological stability of aquatic species, frequently compromising immune defenses and elevating mortality rates. This study was conducted to elucidate the non-specific immune responses induced by Pallisentis (Neosentis) celatus infection in Monopterus albus, with a focus on intestinal histopathology and transcriptome gene expression. A histopathological examination revealed minor alterations in intestinal villi under low-level infection. A transcriptome analysis, performed using Illumina sequencing technology, identified 347 upregulated and 298 downregulated genes involved in critical biological pathways, such as lipid metabolism, immune responses, and the regulation of inflammatory processes. GO and KEGG analyses indicated the upregulation of immune-related pathways, including the RIG-I-like and IL-17 signaling pathways, highlighting a robust intestinal immune response. Conversely, the complement pathway was found to be downregulated, with significant suppression of C9, suggesting that the parasite may engage in immune evasion. Fluorescein-labeled C9 antibody assays confirmed reduced complement C9 levels in the infected tissues. A real-time PCR analysis identified the differential expression of eight genes, including C5, maats1, CFI, and gmnc, which were consistent with the sequencing results. These findings suggest that Pallisentis (Neosentis) celatus infection compromises intestinal health, induces inflammation, and activates non-specific immune responses in Monopterus albus. However, Pallisentis (Neosentis) celatus appears to evade the host immune response by suppressing the activation of complement components, thereby facilitating its reproductive parasitism.